E-learning and social media: Using Facebook to create an online community among applied social practice postgraduate students during a COVID-19 lockdown - Rangiwai, Byron (Te Kaharoa, 2021)
This paper will discuss the use of Facebook as a means for creating an online community to support e-learning among applied social practice postgraduate students in the School of Healthcare and Social Practice at Unitec Institute of Technology during a lockdown in Auckland which began on 17 August 2021 and ended on 3 December 2021 (with the implementation of the COVID-19 Protection Framework see: https://covid19.govt.nz/traffic-lights/covid-19-protection-framework/).